Assessment of Indoor Air Quality in Classrooms and Wellbeing of Teachers in Schools of Hamburg, Germany - Preeti Vishnani (2019)
Background and aims: Problems such as poor indoor air quality (IAQ) and inadequate ventilation are common in schools. These can cause various health problems in students and teachers and ultimately affect their wellbeing. The present study was conducted to assess the indoor air quality in schools of Hamburg, Germany and the subjective perception of teachers about the indoor air quality in schools and work climate and wellbeing status. Materials and Method: The indoor air quality parameters such as temperature, air velocity, relative humidity and CO2 were assessed using a multifunctional device (testo 480) in 21 classrooms in 5 schools of Hamburg from April-July 2017. Noise in the classroom was measured using Sound Level Meter PCE-322A. A questionnaire was developed in German language targeting the school teachers to collect the data regarding the perception of room climate and work climate in the school, and to identify common health complaints among them and their WHO-5 wellbeing index score. Results: Mean temperature, air velocity, relative humidity and CO2 levels were 24.7 ± 1.84 °C, 0.09 ± 0.03 m/s, 54.2 ± 69.9 %, 995.12 ± 432.26 ppm, respectively. Often the teachers encountered the indoor air problems such as high and low room temperature, stuffy air, noise due to students, changing room temperature and unpleasant smell. Fatigue followed by hoarseness/cough were the common health complaints among the study respondents. The mean WHO-5 wellbeing index score was 54.19 ± 17.64. Around 39% of the study participants had below normal (0-50) WHO-5 well-being score. Conclusion: The indoor air quality in the studied classrooms was found to be medium air quality accordance with DIN EN 13779: 2007-09. However, this data complies to spring /summer season and cannot be generalised due to its limitations. Also, further research is needed to assess the well-being status of teachers and the association between the indoor air quality and wellbeing.